Malawi Economy: Population, GDP, Inflation, Business, Trade, FDI, Corruption - The Heritage Foundation (2022)
Learn more about the Malawi economy, including the population of Malawi, GDP, facts, trade, business, inflation and other data and analysis on its economy from the Index of Economic Freedom published by The Heritage Foundation.